Vanellus chilensis - Fernandez, Juan Manuel; Thomann, Luz; Fandiño, Blas; Cajade, Rodrigo; Hernando, Alejandra (Zenodo, 2021)
Vanellus chilensis (Molina, 1782) Figure 5E New records. ARGENTINA • Multiple (no sexual dimorphism); Corrientes, La Cruz, Paraje Tres Cerros; 29° 06′19′′S, 056°55′37′′W. Very common and widespread species in the study site. We recorded several individuals in open grounds and near the farmland. Identification. Widely known. Identified by filamentous crest; breast and forehead black. : Published as part of Fernandez, Juan Manuel, Thomann, Luz, Fandiño, Blas, Cajade, Rodrigo & Hernando, Alejandra, 2021, An annotated checklist of birds of Paraje Tres Cerros, Corrientes province, Argentina, pp. 415-443 in Check List 17 (2) on page 428, DOI: 10.15560/17.2.415